2021
DOI: 10.1021/jacs.1c07235
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Secondary Binding Pocket Promotes Heteromultivalent Targeting of DC-SIGN

Abstract: Dendritic cells (DC) are antigen-presenting cells coordinating the interplay of the innate and the adaptive immune response. The endocytic C-type lectin receptors DC-SIGN and Langerin display expression profiles restricted to distinct DC subtypes and have emerged as prime targets for next-generation immunotherapies and anti-infectives. Using heteromultivalent liposomes copresenting mannosides bearing aromatic aglycones with natural glycan ligands, we serendipitously discovered striking cooperativity effects fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…First, we verified the assay using mannose as a reference (Figure S1A). 45 Since mannose and S36 share the same binding site, a full competition curve can be observed, and the affinity of mannose (K i = 2.4 ± 0.8 mM) is in line with previous reports. 45 Then we performed a titration of compound 1 over a concentration range within its solubility range (850 μM) (Figure S2B).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…First, we verified the assay using mannose as a reference (Figure S1A). 45 Since mannose and S36 share the same binding site, a full competition curve can be observed, and the affinity of mannose (K i = 2.4 ± 0.8 mM) is in line with previous reports. 45 Then we performed a titration of compound 1 over a concentration range within its solubility range (850 μM) (Figure S2B).…”
supporting
confidence: 91%
“…45 Since mannose and S36 share the same binding site, a full competition curve can be observed, and the affinity of mannose (K i = 2.4 ± 0.8 mM) is in line with previous reports. 45 Then we performed a titration of compound 1 over a concentration range within its solubility range (850 μM) (Figure S2B). While the R 2,obs value gradually decreased from 30 to 300 μM of 1, full competition was not observed, suggesting that even though 1 can compete with the reporter molecule, it does not lead to full inhibition of the carbohydrate binding site.…”
supporting
confidence: 91%
“…Over the past decade we 12 and others 13 have reported on the development of DC-SIGN ligands as inhibitors of DC-SIGN mediate viral infections. To the best of our knowledge, however, no ligands have been reported to bind to L-SIGN.…”
mentioning
confidence: 99%
“…Another promising concept to point out is the engagement of secondary binding pockets of carbohydrate lectin receptors (CLRs) in addition to the common homomultivalent targeting of the primary carbohydrate binding site (CBS), as previously studied. The incentive and the future perspectives here are to leverage avidity effects and allosteric regulation and to achieve higher receptor specificity, bypassing the overlapping glycan recognition profiles of lectins. In 2021, Rademacher et al identified a secondary carbohydrate binding site of the C-type lectin receptor DC-SIGN, which can be exploited by heteromultivalent avidity enhancement . They prepared liposomes heteromultivalently decorated with mannose and mannosides bearing an aromatic aglycone, which showed a more avid binding to DC-SIGN + cells compared to the corresponding homomultivalent liposomes.…”
Section: Applicationsmentioning
confidence: 99%
“…In 2021, Rademacher et al identified a secondary carbohydrate binding site of the C-type lectin receptor DC-SIGN, which can be exploited by heteromultivalent avidity enhancement. 152 They prepared liposomes heteromultivalently decorated with mannose and mannosides bearing an aromatic aglycone, which showed a more avid binding to DC-SIGN + cells compared to the corresponding homomultivalent liposomes. The underlying mechanisms were then investigated by combining NMR spectroscopy, molecular docking, and molecular dynamics simulations, revealing two binding modes: a Ca 2+ -dependent interaction with DC-SIGN's CBS and binding to a remote, secondary pocket.…”
Section: Polymeric Glyconanoparticlesmentioning
confidence: 99%